(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1997)
Dasycladalian assemblages collected from Middle-Late Triassic carbonate rocks of the Brenta Dolomites (giudicarie Alps) are illustrated and described. Particular attention is devoted to reproductive organs of Dasycladales observed in one sample coming from the Rhaetian sequence of Croz dell’Altissimo. A new parataxon Terquemella brentai n.sp.is established.